Pasien Positif Covid-19 sebagai Liyan dalam Perspektif Etika Sartre - Bonivasius Korain; Yohanes Batista Abi (Forum, 2023)
The theme of this research is "Covid-19 Patients as Lyan in Sartre's Perspective." This research was born from the struggle of researchers over the fact that in the current pandemic period, a lot of unfair behavior appears and undermines life with the community. This unfair behavior is especially experienced by Covid-19 patients in Malang. In this study, researchers want to conduct a comparative study of dehumanizing behavior towards Covid-19 patients in Malang in Sartrean Ethics. The methodology used in this research is qualitative research with field research. The theoretical basis in this study is the Lyan concept in Jean Paul Sartre's ethics which is compared with the dehumidification behavior of Covid-19 patients in Malang. The research data were obtained through interviews with three research subjects and supported by several realities from supporting sources. This study found that Covid-19 patients had been used as Other by members of the public. Covid-19 patients are referred to as other because they often receive dehumanizing treatment from the community. Their families are also often treated unfairly by being expelled, berated, and humiliated even though they are part of the local community, and they are not Covid-19 patients either.